2010
DOI: 10.1038/npre.2010.5404
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous Capture and Mineralization of Flue Gas Carbon Dioxide: Pilot Scale Study

Abstract: -Multiple CO 2 capture and storage (CCS) processes are required to address anthropogenic CO 2 problems. However, a method which can directly capture and mineralize CO 2 at a point source, under actual field conditions, has advantages and could help offset the cost associated with the conventional CCS technologies. The mineral carbonation (MC), a process of converting CO 2 into stable minerals (mineralization), has been studied extensively to store CO 2 . However, most of the MC studies have been largely invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…For example, CaO has been found to be carbonated on a time-scale of one minute at temperatures above 550°C [49]. However, if the temperature is raised too much, the solubility of CO 2 in water is lowered since the higher kinetic energy causes more motion in molecules which breaks the intermolecular bonds between CO 2 and water, and allows CO 2 to escape from the solution [50][51][52][53]. In this way, the chemical equilibrium is shifted such that free CO 2 is favoured over the bound form.…”
Section: Reaction Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…For example, CaO has been found to be carbonated on a time-scale of one minute at temperatures above 550°C [49]. However, if the temperature is raised too much, the solubility of CO 2 in water is lowered since the higher kinetic energy causes more motion in molecules which breaks the intermolecular bonds between CO 2 and water, and allows CO 2 to escape from the solution [50][51][52][53]. In this way, the chemical equilibrium is shifted such that free CO 2 is favoured over the bound form.…”
Section: Reaction Temperaturementioning
confidence: 99%
“…However, for materials of low solubility in which CaO is bound as silicates, the accelerated carbonation is best carried out in a slurry phase with a liquid-to-solid ratio of greater than one [38,51]. Reddy et al [53] examined the possibility of point-source capture of the flue gas CO 2 with coal FA generated in the same plant [37]. They found that the moisture content of the flue gas is the most important factor that governs the mineralization of the FA particles.…”
Section: Alkaline Solid Waste Materials Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mineral carbonation is being studied at length for its utility in biomineralization of CO 2 from flue gas. Some pilot scale studies have already been undertaken to demonstrate the viability of the process (Reddy et al, 2010 ).…”
Section: Carbon Capture and Storage (Ccs)mentioning
confidence: 99%
“…Similar results were obtained using either seawater or dilute NaHCO 3 as the carrier solution. 94 • A recent patent and results presented by Reddy et al 95,96 involves a method of simultaneously sequestering and storing Hg, SO 2 , and CO 2 by reacting an alkaline material (e.g. fl y ash from a coal-fi red plant, steel slag, paper mill waste ash) with a fl ue gas containing these species.…”
Section: Large-scale Application Of Co 2 Mineral Sequestrationmentioning
confidence: 99%